Red Light Revolution: Harnessing Photobiomodulation for Peak Athletic Performance and Systemic Healing - Słuchocka, Joanna; Lewalski, Tymon; Florczyk, Martyna; Płuciennik, Lidia; Lewalski, Oskar; Jeruć, Klaudia (Quality in Sport, 2026)
Background. Photobiomodulation (PBM), or red light therapy (RLT), involves the application of non-ionizing light to biological tissues to obtain physiological changes. While historically used for wound healing, its role in systemic medicine and athletic performance has recently expanded. Aim. This review aims to evaluate the multi-systemic clinical indications of PBM, ranging from sports performance and recovery to neurology, endocrinology, chronic pain management and others. Methods. A comprehensive literature review was conducted using PubMed and Google Scholar, focusing on peer-reviewed clinical trials and systematic reviews (2003–2024) regarding red and near-infrared light applications. Results. Evidence suggests that PBM stimulates cytochrome c oxidase, increasing ATP production and modulating oxidative stress. Clinical outcomes include reduced muscle fatigue, accelerated bone and tendon repair, neuroprotective effects in brain injury, and significant reduction in chronic inflammatory markers. Conclusions. PBM is a versatile, non-pharmacological intervention that can be utilized to prepare athletes for peak performance, accelerate recovery from soft-tissue and neurological injuries and treat a broad spectrum of clinical pathologies. Success in clinical and athletic settings is highly dependent on adhering to specific wavelength and energy density (dosimetry) protocols.